Synergetic effect of two halogen promoters present in acidic reaction medium or catalyst on the H2O2 formation (in H-2-to-H2O2 oxidation) and destruction over Pd/C (or Al2O3) catalyst - Choudhary, Vasant R.; Jana, Prabhas (Journal of Catalysis, 2007)
A strong synergetic effect of two different halide anions (F- and I-, Cl- and I-, Cl- and Br-, and F- and Br-) at optimum concentration in the catalyst or in an acidic reaction medium was observed in the H-2-to-H2O2 oxidation over Pd/C, Pd/Al2O3, and halogenated Pd/Al2O3 catalysts. The synergetic effect promote, the net H2O2 formation by inhibiting the H2O2 decomposition and hydrogenation reactions. The effect is most pronounced for the combination of fluoride (or chloride) and iodide anions. The Br (1 wt%)-F (1 wt%)-Pd (5 wt%)/Al2O3 catalyst showed very high H2O2 yield (59%)/selectivity (60%) in the H-2-to-H2O2 oxidation. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: H-2-to-H2O2 oxidation; H2O2 decomposition H2O2 hydrogenation; halogen promoter; Hydrogen peroxide; Pd/Al2O3; Pd/C; synergetic effect

Binary mixtures of aprotic and protic ionic liquids demonstrate synergistic polarity effect: an unusual observation - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2020)
In this communication, we demonstrate the solute-solvent and solvent-solvent interactions in the binary mixtures of two aprotic ionic liquids, namely 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, with the protic ionic liquid 1-methylimidazolium acetate. The synergistic effects as expressed by the solvatochromic parameter are noted. This observation is in contrast to the mixing of protic ionic liquids 1-methylpyrrolidium acetate and 4-methylmorpholine acetate with 1-methylimidazolium acetate, respectively. It appears that the synergistic effects in the binary mixtures of aprotic and protic ionic liquids are caused by the formation of hydrogen bonds, since cations are dominant H-bond donors while anions are dominant H-bond acceptors. Preferential solvation models are used to describe the solute-solvent interactions in the binary ionic liquid mixtures.
Keywords: binary mixture; Ionic liquid; polarity; Preferential solvation; synergetic effect